Toward Industry 5.0: A WebSocket–S7 Bridge for Low-Latency, IEC 61588-Compliant Digital Twins in Remote Industrial Automation - Mohammed Hlayel; Hairulnizam Mahdin; Mohammad Hayajneh; Heru Nurwarsito (PLoS ONE, 2026)
While Industry 4.0 established connectivity and automation as foundations of smart factories, the emerging vision of Industry 5.0 emphasizes human-centric, resilient, and sustainable systems. Within this evolution, integrating Digital Twins (DTs) with Programmable Logic Controllers (PLCs) in cloud environments remains constrained by the lack of communication protocols that satisfy strict real-time requirements. To address this gap, this paper introduces and validates a WebSocket–S7 protocol bridge for low-latency, full-duplex communication between Siemens S7 PLCs and cloud-hosted DT models. The main contribution of this work is the design and experimental validation of a lightweight, event-driven WebSocket–S7 architecture. This architecture decouples real-time PLC execution from cloud-based digital twin interaction, enabling deterministic performance over wide-area networks without relying on brokers or polling mechanisms. A comprehensive evaluation compares the proposed bridge with MQTT, OPC UA, and Modbus for real-time PLC–DT interactions managed through Node-RED. Using AWS as the cloud backend, the study assesses performance, scalability, and stability under single-user and multi-user emulated loads. Protocols were profiled using JMeter (load and latency), Wireshark (packet traces), and the Unity Profiler (CPU/memory on Android), with timing judged against IEC 61588 ( ≤ 100 ms ). In remote cloud deployment, WebSocket–S7 achieved an average round-trip time (RTT) of 87 ms, remaining within the IEC 61588 threshold. It outperformed alternative protocols by clear margins—34.6% lower RTT than MQTT (133 ms), 46.3% lower than OPC UA (162 ms), and 55.2% lower than Modbus (194 ms), yielding absolute gains of 46, 75, and 107 ms, respectively. Under multi-user emulation, WebSocket–S7 maintained sub-100 ms average response times for up to 40 concurrent users with near-zero error rates, while MQTT offered a balanced option for moderate-throughput scenarios. These trends reflect WebSocket’s lightweight framing and persistent, broker-less transport. Together, these characteristics minimize connection overhead and jitter in WAN conditions. The findings position WebSocket–S7 as a lightweight and scalable solution for remote DT–PLC integration, particularly when standardized protocols incur higher overhead. By consistently meeting IEC-compliant timing requirements, the proposed bridge provides a practical and robust foundation for deploying real-time digital twins in both educational and industrial automation settings.